Spatiotemporal patterns in ecology and epidemiology [compact disc]: theory, models, and simulation - Malchow, Horst, 1953-; Petrovskii, Sergei V.; Venturino, Ezio (Boca Raton, FL : Chapman & Hall/CRC, 2008)
42